VOCABULARY LEARNING STRATEGIES APPLIED BY EFL LOW AND HIGH ACHIEVERS - Nur Laelatun Chamidah (Universitas Galuh, 2021)
This study aimed at investigating vocabulary learning strategies (VLSs) applied by EFL low and high achievers and how they applied it. The writer employed a case study conducted in two senior high schools in Ciamis. There were 60 participants involved in this study consisted of 30 low and 30 of high achievers. To answer the research questions, the writer conducted semi-structured interview and administered closed-ended questionnaire based on Schmitt (1997)’s classifications of vocabulary learning strategies. From the results of completed questionnaire, the writer found that metacognitive, determination, and memory strategies were the mostly applied by EFL low and high achievers. Those strategies included using English media, consulting on bilingual dictionary, and studying a sound of word. Furthermore, the data of interview specifically showed that watching subtitled films, listening English songs, consulting on google translate, and asking friends are also involved. Finally, EFL low and high achievers have to be aware of their own preferred strategies in learning vocabulary to improve their foreign language learning. It is suggested for English teachers to facilitate students in applying their preferred strategies in learning vocabulary. Keywords: good language learner, low and high EFL achievers, vocabulary learning strategies